Experimental study on RCS joints composed of the CECFST column under lateral cyclic loading - Lee, Wen Yi (Nanyang Technological University, 2021)
The structural performance of joints between reinforced concrete (RC) columns and steel (S) beam under seismic loading is studied in this project. A new form of steel-reinforced concrete columns called concrete-encased concrete-filled steel tubular (CECFST) columns are used to replace the conventional RC columns in this project. In the experimental study, a total of 2 different joint details were studied for the steel beam-to-CECFST column composite joints. Furthermore, two finite element models were established by using ABAQUS software. The main challenges for constructing the RCS frame system consisting of reinforced concrete (RC) columns and steel (S) beams with a steel beam-to-CECFST column is the stirrups at the joint connections as the contractor has to drill tiny holes on the steel beam web with the purpose that the stirrups can pass through the steel beam. Besides, drilling of tiny holes is also needed on the flange of the steel beam for the reinforcing bars of the column to pass through. However, these holes may decrease constructability and it is difficult to deploy this system in real-life applications. In this study, the stirrups are removed at the joint core area and avoid column reinforcing bars passing through the flange of the steel beam to increase constructability of this structural system. In addition, the use of the CECFST column can further improve structural performance. Instead of using stirrups in the joint core area, the joint core was confined by the Face Bearing Plate (FBP) in the second specimen. The advantages of using the FBP at the joint core area are also discussed in this report. From this study, the combination of steel beams and CECFST columns can help improve productivity and constructability in the construction site. On the other hand, this combination can reduce the usage of constructional material. Furthermore, the RCS frame system composed of the CECFST column can be designed as precast components which will decrease the demand of workers on construction site and improve the safety of the construction site. With these, it is hoped that the combination of CECFST column and steel beam in the RCS frame system can be adopted in actual construction sites in the future.